Estudo de adaptação de processos em furadeira CNC para aumento de capacidade produtiva - Rocha, Tiago de Lima (Brasil, 2021)
Industries today are increasingly expanding their production and the growth of their units. The search for competitiveness and increasing profits create a need for companies to triumph over their competitors. In view of this situation, the idea arose to develop this work, which exposes the need to expand the productive capacity of industrial processes in the area of machining of alloy wheels of company objective of study, considering that the current productive capacity cannot supply the expected production demand for the coming years. It deals with the history of the emergence of machining, as well as its concept and, more specifically, the concept of the wheel drilling process, equipment used in this manufacturing process, tools and CNC programming of machining machines. The main variants surrounding the studied theme are also exposed, aiming to gather all the information necessary to carry out the study. It is also documented the development and adaptation process of a light alloy wheel drill, which was used in another machining process, and which is necessary to obtain the desired production increase, where it is currently unused within the company, due to its cost reduction study, thus obtaining na increase in production, which is nowadays the main goal of the company to meet its growing production volume.